Complexity characterization in modeling anisotropic compact stellar structures - Shyam Das; Megandhren Govender; Somi Aktar (European Physical Journal C: Particles and Fields)
Abstract In this study, we present an exact solution to the Einstein field equations, featuring a static, spherically symmetric, anisotropic compact stellar fluid sphere with non-zero complexity. The model is constructed using a specific metric potential for the $$g_{tt}$$ g tt component, along with a defined complexity profile. The model parameters are fixed by ensuring the continuity of the interior and exterior metrics across the surface of the star and by setting the radial pressure to zero across the boundary. The stability of the model has been analyzed by verification of different standard conditions. Validation of our model is supported by recent observational data from well-known pulsars.